Electromyographyc evaluation of complete denture wearers using the balancing ramps concept - Daniel Filgueiras Ferreira; Marcelo Ferraz Mesquita; Frederico Augusto Peixoto Silva; Wagner Araújo Negreiros; Rafael Leonardo Xediek Consani; Guilherme Elias Pessanha Henriques (Universidade Estadual de Campinas, 2016)
This study verified through electromyography the masticatory muscle behavior resulting of the balancing ramps technique to obtain balance in double complete dentures. Eleven totally edentulous patients that used their complete dentures for 5 years at least, had new other ones made and balanced by the balancing ramp technique. The electromyographyc (EMG) activity pattern was registered in anterior temporal (T) and masseter (M) muscles in the rest position (R) and in the maximal voluntary contraction in the intercuspal position (MVCIP), using Myosystem I® (Prosecon Ltda., Uberlândia, MG, Brazil), in four experimental moments: T0 - before the prostheses installation; T1 - 1 month after installation; T2 - 2 months after installation; T3 - 3 months after installation. Results showed a symmetry reduction between T muscles and a little increasing between M muscles in the R position. In the MVCIP position, it there was a reduction for both T and M muscles. The F test showed no statistical significant differences (p<0.05). Authors concluded that the employed technique promote no balance of the masticatory muscles in the tested experimental moments.